Characterization of Outer Membrane Proteome of Akkermansia muciniphila Reveals Sets of Novel Proteins Exposed to the Human Intestine - Ottman, Noora; Huuskonen, Laura; Reunanen, Justus; Boeren, Sjef; Klievink, Judith; Smidt, Hauke; Belzer, Clara; de Vos, Willem M. (Frontiers in Microbiology, 2016)
Akkermansia muciniphila is a common member of the human gut microbiota and belongs to the Planctomycetes-Verrucomicrobia-Chlamydiae superphylum. Decreased levels of A. muciniphila have been associated with many diseases, and thus it is considered to be a beneficial resident of the intestinal mucus layer. Surface-exposed molecules produced by this organism likely play important roles in colonization and communication with other microbes and the host, but the protein composition of the outer membrane (OM) has not been characterized thus far. Herein we set out to identify and characterize A. muciniphila proteins using an integrated approach of proteomics and computational analysis. Sarkosyl extraction and sucrose density-gradient centrifugation methods were used to enrich and fractionate the OM proteome of A. muciniphila. Proteins from these fractions were identified by LC-MS/MS and candidates for OM proteins derived from the experimental approach were subjected to computational screening to verify their location in the cell. In total we identified 79 putative OM and membrane-associated extracellular proteins, and 23 of those were found to differ in abundance between cells of A. muciniphila grown on the natural substrate, mucin, and those grown on the non-mucus sugar, glucose. The identified OM proteins included highly abundant proteins involved in secretion and transport, as well as proteins predicted to take part in formation of the pili-like structures observed in A. muciniphila. The most abundant OM protein was a 95-kD protein, termed PilQ, annotated as a type IV pili secretin and predicted to be involved in the production of pili in A. muciniphila. To verify its location we purified the His-Tag labelled N-terminal domain of PilQ and generated rabbit polyclonal antibodies. Immunoelectron microscopy of thin sections immunolabeled with these antibodies demonstrated the OM localization of PilQ, testifying for its predicted function as a type IV pili secretin in A. muciniphila. As pili structures are known to be involved in the modulation of host immune responses, this provides support for the involvement of OM proteins in the host interaction of A. muciniphila. In conclusion, the characterization of A. muciniphila OM proteome provides valuable information that can be used for further functional and immunological studies.